2021
DOI: 10.15537/smj.2021.42.5.20210022
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of vancomycin powder in total knee arthroplasty

Abstract: Objectives: To assess the efficacy of vancomycin powder (VP) in total knee arthroplasty (TKA). Methods: The study design was retrospective cohort. All patients who underwent primary TKA for osteoarthritis between January 1, 2018, and March 1, 2020, in King Abdulaziz Medical City, Riyadh, Saudi Arabia were included (n=98). Of the total participants, 48 participants in the experimental group matched with 48 participants in the control group were included in the final stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The publication years of the included articles ranged from 2008 to 2023. Among them, 8 articles compared ALBC with negative control (NC) [23][24][25][26][27][28][29][30], 9 articles compared chlorhexidine bathing with NC [31][32][33][34][35][36][37][38][39], 4 articles compared povidone iodine lavage with NC [40][41][42][43], and 14 articles compared vancomycin with NC [13,[44][45][46][47][48][49][50][51][52][53][54][55][56]]. In addition, 2 articles compared chlorhexidine and povidone iodine bathing [57,58], and 1 article compared povidone iodine bathing, vancomycin powder and NC [59].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The publication years of the included articles ranged from 2008 to 2023. Among them, 8 articles compared ALBC with negative control (NC) [23][24][25][26][27][28][29][30], 9 articles compared chlorhexidine bathing with NC [31][32][33][34][35][36][37][38][39], 4 articles compared povidone iodine lavage with NC [40][41][42][43], and 14 articles compared vancomycin with NC [13,[44][45][46][47][48][49][50][51][52][53][54][55][56]]. In addition, 2 articles compared chlorhexidine and povidone iodine bathing [57,58], and 1 article compared povidone iodine bathing, vancomycin powder and NC [59].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…This study also concluded that VP should not be used in primary TKA to prevent PJI 19 . In a single center study of 98 patients, Aljuhani et al did not find a significant difference in infection rates after primary TKA when using intrawound VP 24 . In a separate retrospective cohort study of patients undergoing TKA and THA, Matziolis et al found that although a small difference in PJI risk was observed in the group with local vancomycin compared with the control group, it was not statistically significant 25 .…”
Section: Total Hip Arthroplasty and Total Knee Arthroplastymentioning
confidence: 94%
“…After primary TKA, the prevalence of periprosthetic joint infection (PJI) according to recent studies is 2% and increases to 5.6% after revision TKA 19 . Some studies have shown reduction in PJI after administering VP in the surgical wound before closure of the capsule [20][21][22] , whereas others have not found a statistically significant benefit 19,23,24 .…”
Section: Total Hip Arthroplasty and Total Knee Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative deep wounds are a cause for significant concern, as infections in the surgical site can result in prolonged hospitalization, increased financial burden for the patient and elevated mortality rates (3). Prosthetic joint infection is one of the most dangerous complications of TKA surgery and the most important reason for the revision of TKA (4). Studies have shown that deep infections occur in 1.1% to 1.7% of TKA surgeries (5).…”
Section: Introductionmentioning
confidence: 99%